Importance of anorectal manometry after definitive surgery for Hirschsprung's disease in children - Suzi Demirbag; Tugrul Tiryaki; Tarik Purtuloglu (Wolters Kluwer Medknow Publications, 2013)
Objectives: The purpose of this investigation is to evaluate anorectal function after definitive surgery for Hirschsprung's disease (HD) by anorectal manometry. Materials and Methods: We evaluated the anorectal manometric assessment of 18 children who were operated for HD. Functional outcomes were determined by a questionnaire. Rectoanal inhibitory reflex (RAIR) and maximum anal resting pressure (MARP) were monitored. The results were compared between obstructive patients and asymptomatic patients. Results: The median age at definitive operation was 19 months (range 12-72 months). Anorectal manometry was performed in 14 male and 4 female patients. All the cases underwent three staged procedure for HD and modified Duhamel procedure was performed as definitive procedure for all the patients. Mean age was 4.3 months (range 25 days to 5 years) at time of diagnosis. Post-operative enterocolitis or severe constipation was observed in seven patients (38.8%). There were no patients with incontinence. Eighteen patients underwent anorectal manometry meanly 2 years after definitive operation. RAIR was absent in 14 (77.7%) patients and abnormal in 4 (22.2%). There were no significant differences in the MARP values between symptomatic and asymptomatic patients. Conclusion: The results of our study showed that the majority of the patients have impaired anorectal motility. There were no significant differences in the results of the functional studies for the seven patients with symptoms of obstruction or constipation when compared with asymptomatic patients after surgery for HD.